Health-related quality of life in patients with nasal prosthesis - Becker, Christoph Peter; Becker, Anna-Magdalena; Pfeiffer, Jens (Journal of cranio-maxillofacial surgery, 2016)
Objective - To evaluate the health-related quality of life (QOL) in patients with nasal prosthesis after tumour resection with partial or total rhinectomy. - Material and methods - Patients with nasal prosthesis were asked to complete a quality of life questionnaire. 43 patients with prosthesis after partial or total rhinectomy completed the University of Washington quality of life questionnaire. Answers were systematically analysed. - Results - 27 patients were male, 16 were female. Mean age was 62 years, and the mean interval between tumour resection and date of study inclusion was 45.3 months. There are gender-specific differences for the QOL domain ‘recreation’ and age-specific differences for the domains ‘appearance’ and ‘saliva’. The fields ‘activity’, ‘mood’ and ‘appearance’ are the most severely affected QOL domains in patients with nasal prosthesis. - Conclusion - Similar to other head and neck cancers there is a need and a deficiency in psycho-oncological support after partial or total rhinectomy, the influence on QOL however was much lower than initially expected. This should be considered with regard to the oncological benefits of this surgical procedure. Compared to the results of other head and neck malignancies the ‘appearance’ is only slightly affected. A stable prosthesis is needed to enable the maintenance of the accustomed activities.